1993
DOI: 10.1073/pnas.90.8.3329
|View full text |Cite
|
Sign up to set email alerts
|

Odor-induced increases in c-fos mRNA expression reveal an anatomical "unit" for odor processing in olfactory bulb.

Abstract: Expression of the immediate-early gene c-fos was used to evaluate the coordinate activation of olfactory bulb neurons by brief exposure to specific odors in the alert rat. In situ hybridization to c-fos mRNA was compared to regional increases in 2-deoxy-D-[14C]glucose incorporation in an adjacent section analysis. Levels of c-fos mRNA in olfactory bulb were high in rats recently removed from their home cage but were low in animals placed in a relatively odor-free chamber for 30 min. Presentation of specific od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
161
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(175 citation statements)
references
References 43 publications
(40 reference statements)
13
161
1
Order By: Relevance
“…Because c-fos mRNA increases essentially as if it were an integral of electrical activity, and because the olfactory response adapts, the majority of the c-fos signal would be expected to arise from the first minute of exposure in each repeated 3 min exposure. Moreover, Guthrie and Gall (1993) demonstrated that rats exposed to peppermint odor for 5 min displayed c-fos activation patterns similar in extent (albeit more noisy) than the pattern displayed by rats exposed to peppermint odor for 30 min. We contend that we are measuring the response during the first several minutes of exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because c-fos mRNA increases essentially as if it were an integral of electrical activity, and because the olfactory response adapts, the majority of the c-fos signal would be expected to arise from the first minute of exposure in each repeated 3 min exposure. Moreover, Guthrie and Gall (1993) demonstrated that rats exposed to peppermint odor for 5 min displayed c-fos activation patterns similar in extent (albeit more noisy) than the pattern displayed by rats exposed to peppermint odor for 30 min. We contend that we are measuring the response during the first several minutes of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The antisense c-fos cRNA was transcribed from a mouse recombinant cDNA clone to generate a 535 base transcript corresponding to positions 1842-1944 and 2061-2493 of the mouse c-fos gene. Increases in c-fos mRNA were measured in the juxtaglomerular cells (periglomerular and external tufted cells) surrounding glomeruli (Guthrie et al, 1993;Guthrie and Gall, 1995a,b). Glomeruli were scored as positive when an arc of labeled juxtaglomerular cells spanning either 180 o in any orientation or two 90 o arcs spanning any region not abutting the external plexiform layer were identified (Schaefer et al, 2001b).…”
Section: Methodsmentioning
confidence: 99%
“…The localization of pCREB in the dorsolateral region correlates very well to c-fos mRNA expression in response to peppermint odor (Guthrie et al 1993), which was shown to activate periglomerular, mitral, and granule cells in adult rats and to the general region (midlateral) of c-fos activated by retrieval of a conditioned peppermint odor in older pups (Johnson et al 1995). However, in retrieval studies, increases in fos-reactive cells have been associated selectively with the periglomerular region in response to peppermint odors (Guthrie et al 1993;Johnson et al 1995;Schwab 1996).…”
Section: Creb Phosphorylation In Odor-stroke Pairingmentioning
confidence: 96%
“…The localization of pCREB in the dorsolateral region correlates very well to c-fos mRNA expression in response to peppermint odor (Guthrie et al 1993), which was shown to activate periglomerular, mitral, and granule cells in adult rats and to the general region (midlateral) of c-fos activated by retrieval of a conditioned peppermint odor in older pups (Johnson et al 1995). However, in retrieval studies, increases in fos-reactive cells have been associated selectively with the periglomerular region in response to peppermint odors (Guthrie et al 1993;Johnson et al 1995;Schwab 1996). Cell numbers in the periglomerular region (Coopersmith and Leon 1986;Leon 1987, 1991;Sullivan et al 1990Sullivan et al , 1991Matsutani and Leon 1993;Johnson et al 1995), the density of glial processes in the glomeruli ( Matsutani and Leon 1993) and the area of the glomerular neuropil are all increased in pups that have undergone 18 days of conditioning procedures.…”
Section: Creb Phosphorylation In Odor-stroke Pairingmentioning
confidence: 96%
“…), or oleic acid (10 mg kg -1 ) and killed the rats 60 min later by decapitation under anaesthesia. In situ hybridization analyses were conducted using [ 35 S]-labelled antisense RNA probes for c-fos 28 and choline acetyl transferase 29 . Average hybridization densities were determined from at least three tissue sections per rat.…”
Section: In Situ Hybridizationmentioning
confidence: 99%